Assistance in The Implementation of Ovitrap-Larvitrap In Controlling The Aedes Aegypti Mosquito Population For The Prevention of Dengue Fever (DHF) In Elementary Schools, Poasia District, Kendari City - Bakkareng, Wirdhana; Yanti, Nur Arfa; Ardiansyah, Ardiansyah; Amirullah, Amirullah; Ampa, Andi Tenri; Rudia, La Ode Adi Parman (Digital Innovation, 2024)
Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pemahaman guru dalam mengenal kondisi lingkungan yang berpotensi sebagai habitat perkembangbiakan nyamuk Aedes aigypti di lngkungan sekolah dan meningkatkan kemampuan dan keterampilan guru-guru dalam merancang dan memasang alat ovitrap dan larvitrap dengan tepat yang dapat diajarkan kepada siswa-siswanya. Kegiatan pengabdian masyarakat berupa pelatihan pembuatan Ovitrap dan larvitrap untuk memutus siklus hidup nyamuk Aedes bagi guru-guru SD di Kecamatan Poasia Kota Kendari telah dilaksanakan pada tanggal 19 Oktober 2024 yang melibatkan 5 orang dosen dan 6 orang mahasiswa dari FMIPA UHO. Kegiatan dilanjutkan dengan pendampingan pemasangan di lingkungan sekolah masing-masing. Hasil evaluasi menunjukkan bahwa pelatihan tersebut telah meningkatkan kemampuan dalam mengenal berbagai factor penyebab kasus demam berdarah dan terampil dalam membuat ovitrap dan larvitrap sebagai sarana yang tepatbdalam menurunkan populasi nyamuk vector demam berdarah. Kata kunci : Demam berdarah dengue (DBD), Aedes aegypti, Larvi trap. ABSTRACT This community service activity aims to increase teachers' understanding of environmental conditions that have the potential to become breeding habitats for the Aedes aigypti mosquito in the school environment and improve teachers' abilities and skills in designing and installing ovitrap and larvitrap equipment appropriately which can be taught to their students. Community service activities in the form of training in making Ovitrap and larvitrap to break the life cycle of the Aedes mosquito for elementary school teachers in Poasia District, Kendari City were carried out on October 19, 2024 involving five lecturers and six students from FMIPA UHO. The activity continued with installation assistance in each school environment. The evaluation results show that the training has improved the ability to recognize various factors that cause cases of dengue fever and skills in making ovitraps and larvitraps as appropriate means of reducing the population of dengue vector mosquitoes. Key words: Dengue hemorrhagic fever (DHF), Aedes aegypti, Larvi trap